Effect of endemic diseases including trypanosomiasis on the blood packed cell volume of livestock in northern Ivory Coast - Coulibaly, L.; Diarrassouba, I.; D'Ieteren, G.D.M.; Itty, P.; Maehl, H.M.; Mahamat, B.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Schuetterle, A.; Thorpe, W.R.; Trail, J.C.M. (OAU/STRC, 1988)
Studies trypanosome infections and other anaemia producing pathogens in cattle and sheep maintained in village herds and flocks at network sites of Boundiali and tengrela in northern Ivory Coast